A Rosier Reality: Incongruency in Stated and Revealed Ingroup Preferences among Young Asian American Speed Daters. (December 2018) - Wu, Karen; Chen, Chuansheng; Greenberger, Ellen
Several studies have identified inconsistencies between "stated" interpersonal attitudes and those "revealed" after an interaction. The authors used the speed-dating paradigm to examine stated and revealed attitudes in ingroup preferences among Asian American subgroups (Chinese, Korean, Vietnamese, and Filipino Americans). Young single Asian Americans ( n = 198) reported preferences for dating different ethnicities and went on speed dates, after which they could offer second dates to their partners. As expected, all four ethnic subgroups showed clear ingroup biases in stated preferences. Ingroup bias in revealed preferences (measured through date offers and ratings of partners' mate desirability), however, were minimal. At the individual level, stated ingroup preferences did not significantly predict revealed ingroup preferences. In summary, among young Asian Americans, ingroup preferences may not hold in an interactive scenario. The findings suggest that in the presence of personal cues provided through a brief interaction, people may be less prone to make judgments on the basis of ethnicity, even when consequences extend beyond the laboratory. Furthermore, mechanisms for selecting a partner may differ in "hot" (affective) versus "cold" (cognitive) states.